Development of GSM-Based Vehicle Anti-Theft System - Hamid, Khairul Hamzani (2006)
Vehicle theft is a universal problem. The statistic of the vehicle gets stolen or vandalized increases at an alarming rate every year. For example in Malaysia alone, for the year 2004, it was reported that about 26,566 cars were stolen which represents about 33% increases compared to the statistic of the same period of the previous year. This will lead to an increase in the vehicle insurance premium which has to be paid by consumers. Therefore, it can be concluded that the security systems installed by the vehicle manufacturer are not effective enough. To solve this problem, a wireless vehicle security system which implements mobile communication protocol is proposed. The control and communication between the user and the proposed system are achieved through a short message services (SMS) protocol available in the cellular phone. The proposed system is interfaced with an immobilizer and a remote keyless entry system.The proposed system is capable of informing the user through the user's cellular phone if the car is vandalized, tampered or stolen by an intruder. At the same time the remote keyless entry system and the immobilizer systems will activate the alarm. The system will produce human voice instead of producing an alarm sound. By using the proposed system, the user is also capable of controlling the car's door remotely. The effective communication coverage of this system is based on the user's cellular phone coverage. The proposed system consists both hardware and software parts. The hardware components include a microcontroller, an immobilizer, a remote keyless entry (RKE) system, a GSM modem, a voiced-alarm module, a cellular phone and a remote control of the RKE system. The software part includes a program controller interface. The result of simulation and practical tests conducted on the proposed system, demonstrate that the proposed system is successfully designed and fabricated.